Pengembangan E-modul Dasar Listrik dan Elektronika di Sekolah Menengah Kejuruan - Rosi Putri; Elfizon Elfizon (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
This research was motivated by the not yet compiling effective learning materials. So that learning is still teacher-centered and has not yet been created for students to learn independently. Therefore, it is necessary to have teaching materials that support the learning process in utilizing technology, one of which is by using e-modules. This research aims to produce a valid and practical e-module in the Basic Electrical and Electronics Class of the TITLL class at SMK Negeri 1 Pariaman. This research uses a 4-D development model with four stages, namely Define, Design, Develop, and Disseminate. The subjects of this research trial were students of class X TITL at SMK Negeri 1 Pariaman. The data were collected using a validity and practicality questionnaire in the form of a Likert scale which had been validated by an instrument expert lecturer. Data analysis using percentage techniques. The results showed that the validator respondents were two lecturers and one teacher on the validity of the product in the valid category, while the two teacher respondents on the practicality of the product were obtained in the very practical category. Thus, the e-module of Basic Electricity and Electronics was declared valid and practically used as a learning medium for Basic Electricity. and Electronics.